2017
DOI: 10.15244/pjoes/67064
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Distribution and Groundwater Quality Assessment for a Coastal Area on a Chinese Island

Abstract: Chongming Island is located in the lower Yangtze Estuary in China. Due to the Leachate from a refuse landfill and the hydrodynamics of the Yangtze Estuary, the groundwater environment is particularly complicated on Chongming Island. Field observations were carried out around the landfill disposal site. The groundwater table, temperature, pH, salinity, and dissolved oxygen were measured in the field by portable equipment, and 192 water samples were collected at eight groundwater sites and one surface water site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…A number of studies have reported the soil quality of arable land in Chongming District, mainly focusing on the distribution and quality assessment of heavy metals and dissolved OM (Lou et al 2017;Sun et al 2010;Wang et al 2015;Zheng et al 2016). The previous studies together with the results obtained in the present study show that the soil quality of the agricultural land in Chongming District is generally good (Zhang et al 2014;Zheng et al 2016; this study).…”
Section: Discussionsupporting
confidence: 68%
“…A number of studies have reported the soil quality of arable land in Chongming District, mainly focusing on the distribution and quality assessment of heavy metals and dissolved OM (Lou et al 2017;Sun et al 2010;Wang et al 2015;Zheng et al 2016). The previous studies together with the results obtained in the present study show that the soil quality of the agricultural land in Chongming District is generally good (Zhang et al 2014;Zheng et al 2016; this study).…”
Section: Discussionsupporting
confidence: 68%
“…However, excessive concentrations can be toxic to living organisms. Heavy metal contaminants such as chromium (Cr), nickel (Ni), copper (Cu), zinc (Zn), cadmium (Cd), and lead (Pb) are generally more persistent than organic contaminants [4]. Metal nutritional requirements vary substantially among animals or plant species and also differ with a range of element types [5].…”
mentioning
confidence: 99%
“…Besides, a significant positive relation was found between conductivity and heavy metals of Fe and Mn (p<0.01). In similar studies, the strong relationship and the potentiation of metal toxicity via increased water temperature or lowered dissolved oxygen levels were reported (Lou et al, 2017;Hertika et al, 2018). Consequently, the water quality of Kayacik Dam was found to be second class according to SKKY.…”
Section: Resultsmentioning
confidence: 72%